Implementasi Pendidikan Agama Islam sebagai Muatan Lokal di SD Negeri 49 Gresik - Rohman , Rofiq Nur (STAI Ihyaul Ulum Gresik, 2024)
The local content curriculum is a set of plans and arrangements regarding the content and learning materials and methods used as guidelines for organizing teaching and learning activities determined by institutions according to the circumstances and needs of each institution. The phenomenon in the current millennial generation is that their religious character is decreasing due to the influence of free access to anything on the internet. A local content curriculum can strengthen children's religious character to increase their faith and devotion to Allah. And have noble morals in personal, social, national and state life. This study uses a qualitative approach with a case study method. Data were collected through direct observation, in-depth interviews with the principal, Islamic Religious Education teachers, and parents of students, as well as document analysis such as lesson plans and lesson schedules. The study results show that implementing the Islamic Religious Education curriculum at SD Negeri 49 Gresik is carried out with a schedule integrated into the school curriculum and adjusted to regular lesson hours. The learning process includes lecture, discussion, and practice methods, with materials that refer to the established local content curriculum standards. This implementation has a positive impact with good integration in the lesson schedule. However, time adjustments, increased teacher training, and further support from schools and parents are needed to optimize learning. Continuous evaluation and improvement are required to ensure the effectiveness of the curriculum and the optimal achievement of religious education goals.